Rancang Bangun Sistem Pengaman Kebocoran Liquefied Petroleum Gas (LPG) Dan Api Menggunakan Mikrokontroler NodeMCU ESP8266 Berbasis Aplikasi Blynk - Beny, Frederik Beny Silamba; Bambang Widodo, Bambang Widodo; Susilo, Susilo (Prodi Teknik Elektro FT UKI, 2024)
Gas leakage is also one of the security concerns in the surroundings of the house. It is not uncommon to find cases of LPG pipes leaks that result in deaths and losses to its users. To reduce the occurrence of gas leaks then designed a tool that functions as security on the use of automatically integrated LPG tubes. With the MQ-2 Sensor Test 30 trials at 18 trials that succeed at a distance of 25-31 cm. so that it can unlock the rotor on the regulator, the buzzer sounds and sends notifications to the Blynk application. with the IR-Flame Sensor testing 30 trial at 30 tries that work at the distance of 1-30 cm. The security system will only be activated if either of the sensors or both sensors detect a gas leak or a fire occurred when the gas leaks occurred.